2016
DOI: 10.5194/acp-16-6027-2016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varying experimental conditions on the viscosity of <i>α</i>-pinene derived secondary organic material

Abstract: Abstract. Knowledge of the viscosity of particles containing secondary organic material (SOM) is useful for predicting reaction rates and diffusion in SOM particles. In this study we investigate the viscosity of SOM particles as a function of relative humidity and SOM particle mass concentration, during SOM synthesis. The SOM was generated via the ozonolysis of α-pinene at < 5 % relative humidity (RH). Experiments were carried out using the poke-and-flow technique, which measures the experimental flow time … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
156
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(166 citation statements)
references
References 77 publications
8
156
2
Order By: Relevance
“…Oligomer decomposition could be an artifact of the sample preparation and analysis steps after particle collection, or it could be an intrinsic aspect of accretion chemistry that occurs prior to particle collection and analysis. If reversibility is an intrinsic aspect of accretion chemistry, then the higher amounts of low-OSc monomers in large particles suggest that diffusion within the particle phase is hindered (Faulhaber et al, 2009;Grayson et al, 2016;Koop et al, 2011;Renbaum-Wolff et al, 2013) and/or phase separation has occurred (Laskina et al, 2015;Veghte et al, 2013;Virtanen et al, 2011;Werner et al, 2016), effectively trapping the released monomers within the particle and making them unable to re-equilibrate with the gas phase. Reversibility of the oligomerization process provides a reasonable explanation why β-pinene SOA yields are so strongly dependent on temperature and relative humidity (von Hessberg et al, 2009).…”
Section: Molecular Composition Of Size-selected Soamentioning
confidence: 99%
“…Oligomer decomposition could be an artifact of the sample preparation and analysis steps after particle collection, or it could be an intrinsic aspect of accretion chemistry that occurs prior to particle collection and analysis. If reversibility is an intrinsic aspect of accretion chemistry, then the higher amounts of low-OSc monomers in large particles suggest that diffusion within the particle phase is hindered (Faulhaber et al, 2009;Grayson et al, 2016;Koop et al, 2011;Renbaum-Wolff et al, 2013) and/or phase separation has occurred (Laskina et al, 2015;Veghte et al, 2013;Virtanen et al, 2011;Werner et al, 2016), effectively trapping the released monomers within the particle and making them unable to re-equilibrate with the gas phase. Reversibility of the oligomerization process provides a reasonable explanation why β-pinene SOA yields are so strongly dependent on temperature and relative humidity (von Hessberg et al, 2009).…”
Section: Molecular Composition Of Size-selected Soamentioning
confidence: 99%
“…If SVOCs are not well mixed within SOA particles on this timescale, then chemical transport models could incorrectly predict SOA mass concentrations by up to an order of magnitude (Shiraiwa and Seinfeld, 2012) and incorrectly predict the size of SOA particles (Zaveri et al, 2014), with implications for air quality and climate predictions (Seinfeld and Pandis, 2006). Recent research has shown that mixing times of organic molecules within SOA particles can be > 1 h at roomtemperature and at low RHs (Abramson et al, 2013;Grayson et al, 2016;Liu et al, 2016;Perraud et al, 2012;RenbaumWolff et al, 2013;Song et al, 2016;Ye et al, 2016;Zhang et al, 2015). In addition, studies have shown that proxies of SOA particles can form glass at low RHs and low temperatures Zobrist et al, 2008).…”
mentioning
confidence: 99%
“…Järvinen et al (2016) measured the temperature and RH values at which α-pinene SOA has a viscosity of approximately 10 7 Pa s. In these experiments, SOA was generated with a mass concentration of 707-1414 µg m −3 . Grayson et al (2016) measured viscosity of α-pinene SOA as a function of RH at 295 K. In these experiments, the SOA was generated with mass concentrations of 121 and 520 µg m −3 . We use the viscosity measurements from Grayson et al (2016) determined with a mass concentration of 520 µg m −3 to be more consistent with the mass concentrations used by Järvi-nen et al (2016).…”
mentioning
confidence: 99%
See 2 more Smart Citations